IMPLEMENTASI TEKNOLOGI PETA VIRTUAL 3D GEDUNG E TEKNIK SIPIL DAN GEDUNG F LABORATORIUM HIDROLIKA FAKUTAS TEKNIK UNIVERSITAS LAMPUNG - Aristoteles Aristoteles; Maya Asterita; Yunda Heningtyas; Kurnia Muludi; Admi Syarif (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Lampung University doing out routine activities every new academic year for students especially for new students college who majoring in Civil Engineering, Faculty of Engineering, Introduction about Campus Life for New Students (PKKMB), one of the main agendas of PKKMB is introducing about everyvbuildings and public facilities in Civil Engineering also every building and the room in it. The current state of the COVID-19 pandemic make the University of Lampung conduct learning activy by network (online). So, it's make every students activities not possible to perform direct tracing. Serving method information follows technological developments, one of which is 3D visualization techniques. With using the Multimedia Development Life Cycle (MDLC) system development method, 3D virtual map applications can be developed that can display building layouts and facilities in 3D. This research is Alpha Testing and Customer satisfaction. Alpha Testing provides test results The application can operate on versions in operation android system 7.1 to 10. The application can operate on smartphone with screen specifications from 5.0 inch to 6.5 inches. The application can operate on smartphones from minimum 3GB RAM to 8GB RAM. Customer Satisfaction Respondents stated that the 3D Virtual Map Application of Building E Civil Engineering and Building F of the Hydraulics Laboratory get good results with a percentage index between 87.5% to 95%.